Quantitative SWOT analysis for prioritizing ecotourism-planning decisions in protected areas: Igneada case. Issue 5 (2nd September 2016) - Demir, Sara; Esbah, Hayriye; AKGÜN, Aliye Ahu
ABSTRACT: As environmental problems and pressures on natural resources escalate, awareness building and efforts to protect natural areas have also became a major goal to ensure sustainability. Ecotourism is one of the major activities to protect natural and cultural resources, while also providing economic benefits to both local people and government. Successful ecotourism planning is a function of establishing sound goals and criteria. In this paper, we have presented the example of Igneada, Turkey, as a case to elaborate this point. Igneada a coastal town, located on the north-west Black Sea region of Turkey, was declared a national park in 2007. The park is well known for its longos forests (flooded), lagoons, endemic and endangered species, and wildlife. However, currently, unsustainable economic activities, overgrazing, and urbanization cause threats to its sensitive ecosystems. Promoting ecotourism is a sustainable approach to balance economic, social, and environmental aspects in the development of Igneada. The aim of this study is to define a set of ecotourism criteria and propose an ecotourism vision for Igneada. The methodology in this research involves field observations and a strengths, weaknesses, opportunities and threats analysis with an Analytical Hierarchy Process. A survey study is conducted with both local people and experts to define a framework to generate a priority ranking for ecotourism-planning decision. The research generated 5 main criteria and 14 subcriteria, among which 'Proposal of Igneada in Turkey's 2023 Tourism Strategy Plan' was the highest ranked opportunity for ecotourism planning and development in the town.